Does overcapacity prompt controlling shareholders to play a propping role for listed companies? - Cailing Li; Dongjie Lin (China Journal of Accounting Research, 2020)
A major risk currently facing the Chinese economy is overcapacity, which affects the efficiency of social resource allocation (Xi et al., 2017; Huang et al., 2019). When a company is in crisis, the internal capital market often plays a propping role. This study approached this issue from the perspective of the controlling shareholder and examined whether controlling shareholders provide financial support to enterprises in industries with excess capacity. According to the data for China's A-share listed companies from 2007 to 2019, companies in industries with excess capacity received more financial support from controlling shareholders compared with those in non-overcapacity industries. Analysis of the mechanism revealed that state-owned enterprises and companies with relatively poor financial status received more financial support from controlling shareholders. This study also examined the economic consequences of such support and found that it is conducive to enhancing enterprise value. This study enriches the literature on overcapacity and internal capital markets by demonstrating that internal capital markets play a propping role for companies facing industry-level crises. This finding has both theoretical value and practical implications related to supply-side reform and capacity reduction.
Keywords: 650; Overcapacity; Internal capital market; Financial support; Controlling shareholder